An Analysis of the Availability of Lactation Rooms in Makassar Traditional Markets and Its Policy Implications - Sri Yunita Simanjuntak; Fahmi Surya Abdi; Muallim Muallim (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2026)
Lactation rooms in public spaces are a legally guaranteed right of breastfeeding mothers. However, their availability in traditional markets in Makassar City remains very limited. This study aims to analyze the availability, conditions, and factors influencing these facilities in traditional markets in Makassar City. The method used was quantitative descriptive with a cross-sectional design. Secondary data were sourced from the Makassar City Statistics Agency (2022–2024) and the 2023 Indonesian Health Survey (SKI). Meanwhile, primary data was obtained through direct observation at 15 selected traditional markets using a checklist standardized by Minister of Health Regulation No. 15 of 2013. The results of the study indicate that the availability of these facilities is very limited. Only two of the 15 markets (13.3%) have lactation rooms, with only one of these meeting the adequate category. Field findings revealed three main inhibiting factors. These factors include limited physical space (84.6%), management's lack of understanding of regulations (69.2%), and weak law enforcement by relevant authorities. This situation requires serious attention. As a large city, Makassar has a population of 1,423,877 (2023) with a population density of 8,173 people per square kilometer. Meanwhile, national exclusive breastfeeding coverage for children aged 6–23 months is only 55.5%. Therefore, the limited availability of breastfeeding rooms in traditional shopping centers has the potential to hinder the fulfillment of children's and mothers' rights and poses a significant challenge to efforts to increase exclusive breastfeeding targets.